5
$\begingroup$

Prove that $$\left(\frac12(x+y)\right)^2 \leq \frac12(x^2 + y^2)$$

I've gotten that $$\left(\frac12(x+y)\right)^2 \ge 0 $$ but stumped on where to go from here...

$\endgroup$
2
15
$\begingroup$

Proof by picture (angle H is 90°). proof without a word

$\endgroup$
0
11
$\begingroup$

Expand both sides and we have:

$$\frac{x^2 + y^2}{2} \ge \frac{x^2 + 2xy + y^2}{4}$$ $$\iff x^2 + y^2 \ge {2xy}$$ $$\iff (x-y)^2 \ge 0$$

Which is well-know fact.

Also there are lot of other ways to prove it, here's "fancy" one using Cauchy-Scwarz inequality:

$$(1 + 1)(x^2 + y^2) \ge (x + y)^2$$

Multiply both sides by $\frac 14$:

$$\frac 12 (x^2 + y^2) \ge \left(\frac 12 (x+y)\right)^2$$

$\endgroup$
4
  • $\begingroup$ What norm and wich vectors are you applying C-S on? I'm somewhat confused - sorry if it's trivial^^ // Okay see it now. It's $\mathbb R^2$ and the vectors $\begin{pmatrix}1\\1\end{pmatrix}$ and $\begin{pmatrix}x\\y\end{pmatrix}$ $\endgroup$ – AlexR Feb 5 '14 at 21:57
  • $\begingroup$ @AlexR To be fair I'm not familiar too much with vector use of Cauchy-Schwarz, but I think that those are the vectors used. As a contest participant I am more familiar with the use of real values: $$\left(\sum_{n=0}^k x_k^2\right) \cdot \left(\sum_{n=0}^k y_k^2\right) \ge \left(\sum_{n=0}^k x_ky_k\right)^2$$ In this case $x_1 = x_2 = 1$ and $y_1 = x^2$ and $y_2 = y^2$ $\endgroup$ – Stefan4024 Feb 5 '14 at 22:27
  • $\begingroup$ You mean $y_1=x, y_2 = y$ ;) The vector form is more general (because it works on all inner product spaces, not only $\mathbb R^n$) $\endgroup$ – AlexR Feb 5 '14 at 22:29
  • $\begingroup$ @AlexR Yes, you are right $y1=x, y_2 = y$. I might consider getting more familiar with vector form, because as you've mentioned it has much more wider use. $\endgroup$ – Stefan4024 Feb 5 '14 at 22:40
3
$\begingroup$

$\frac12 (x^2+y^2)-(\frac12 (x+y))^2$

$=\frac12 (x^2+y^2)-\frac14 (x^2+y^2+2xy)$

$=\frac14 (2x^2+2y^2-x^2-y^2-2xy)$

$=\frac14 (x^2+y^2-2xy)$

$=\frac14 (x-y)^2\ge 0$

$\endgroup$
0
2
$\begingroup$

This substitution is a nice way to do this:

$$x=r\sin\theta , y=r\cos\theta$$ So, our identity: $$\left(\frac12(x+y)\right)^2 \leq \frac12(x^2 + y^2)$$ $$\frac{1}{4} (x^2+y^2+2xy) \leq \frac12(x^2 + y^2)$$

Applying our substitutions:
$$\frac{1}{4} (r^2+2\cdot r\sin\theta\cdot r\cos\theta) \leq \frac12(r^2)$$ $$\frac{r^2}{2}\cdot \frac{1+\sin2\theta}{2} \leq \frac{r^2}{2}$$

Now, if you note that the maximum value of $\sin 2\theta$ is $1$, then it becomes obvious.

Added: It could have also been done it this way: $$\left(\frac{1}{2}(x+y)\right)^2 \leq \frac12(x^2 + y^2)$$ $$\frac{1}{2}\cdot\frac{1}{2}(r\cos\theta+r\sin\theta)^2 \leq \frac{r^2}{2}$$ $$\frac{r^2}{2}\cdot\frac{1}{2}(\cos\theta+\sin\theta)^2 \leq \frac{r^2}{2}$$

Now, note that $-\sqrt{2} \leq \cos\theta+\sin\theta = \sqrt{2}\cos(x+45^{\circ}) \leq \sqrt{2}$. Thus the maximum value of $(\cos\theta+\sin\theta)^2$ is $2$, and the result follow.

$\endgroup$
1
$\begingroup$

$$(x-y)^2\geq0$$ $$2xy\leq x^2+y^2$$ $$x^2+y^2+2xy\leq 2x^2+2y^2$$ $$(x+y)^2\leq 2x^2+2y^2$$

$\endgroup$
1
$\begingroup$

let investigate $$\frac{(x+y)^2}{4}-\frac{x^2+y^2}{2}=\frac{x^2+y^2+2xy-2x^2-2y^2}{4}=\frac{-(x-y)^2}{4}$$ then it is obvious that we have $$\frac{(x+y)^2}{4}-\frac{x^2+y^2}{2}\leq 0.$$ So $$\frac{(x+y)^2}{4}\leq\frac{x^2+y^2}{2}.$$

$\endgroup$
0
$\begingroup$

Notice that

$$(\frac{1}{2}(x+y))^2=\frac{1}{4}(x^2+2xy+y^2)\leq \frac{1}{4}(x^2+[x^2+y^2]+y^2)$$ (why?)

$\endgroup$
1
  • 1
    $\begingroup$ because x^2 + y^2>=2xy ! thanks $\endgroup$ – Sua Feb 5 '14 at 21:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.